Birds of Pakistan - Grimmett, Richard ; Roberts,Tom ; Inskipp, Tim (London Christopher Helm, 2008)
Birds of Pakistan is a comprehensive field guide to all of the birds of Pakistan. It covers over 670 species including all breeding species, regular visitors and vagrants. 93 colour plates illustrate every distinct plumage of every species with concise text on facing pages. The book includes 600 distribution maps in colour."--Jacket
Include Map, Color Illustrations, Appendix, Tables and Index
Keywords: Pakistan -- Birds -- Birds--Geographical distribution